2020
DOI: 10.3390/catal10010047
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Activity of Ni2P/Desilicated Zeolite β Catalysts for Hydrocracking of Pyrolysis Fuel Oil into Benzene, Toluene, and Xylene

Abstract: The effects of desilication (DS) of the zeolite β on the hydrocracking of polycyclic aromatics were investigated using the Ni2P/β catalysts. The Ni2P/β catalysts were obtained by the temperature-programmed reduction (TPR) method, and the physical and chemical properties were examined by N2 physisorption, X-ray diffraction (XRD), 27Al magic angle spinning–nuclear magnetic resonance (27Al MAS NMR), extended X-ray absorption fine structure (EXAFS), isopropyl amine (IPA) and NH3 temperature-programmed desorption (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 42 publications
(49 reference statements)
0
10
0
Order By: Relevance
“…The H + -exchanged zeolite exhibited superb catalytic performance for catalytic copyrolysis of cork oak with waste polymer, in which HBeta zeolite showed fast pyrolysis activity due to the strong acidity and the appropriate pore diameter [1]. It was also confirmed that the formation of hierarchically nanoporous structure in HBeta zeolite by desilication is useful for giving high catalytic activity in the hydrocracking of large aromatic hydrocarbons, which can be attributed to the good dispersion of Ni 2 P catalysts and efficient accessible acid sites [2]. The acidic zeolite with MFI framework having a hierarchically nanoporous membrane structure exhibited high surface area and good diffusivity, resulting in the high catalytic performance in n-dodecane cracking [3].…”
mentioning
confidence: 81%
“…The H + -exchanged zeolite exhibited superb catalytic performance for catalytic copyrolysis of cork oak with waste polymer, in which HBeta zeolite showed fast pyrolysis activity due to the strong acidity and the appropriate pore diameter [1]. It was also confirmed that the formation of hierarchically nanoporous structure in HBeta zeolite by desilication is useful for giving high catalytic activity in the hydrocracking of large aromatic hydrocarbons, which can be attributed to the good dispersion of Ni 2 P catalysts and efficient accessible acid sites [2]. The acidic zeolite with MFI framework having a hierarchically nanoporous membrane structure exhibited high surface area and good diffusivity, resulting in the high catalytic performance in n-dodecane cracking [3].…”
mentioning
confidence: 81%
“…[ 347 ] Similar mesoporogens with different alkyl chain‐lengths (e.g., TEAOH, TPAOH, TBAOH), were used by several research groups. [ 345,348–351 ] As such, Werner et al. [ 348 ] and Morgado Prates et al.…”
Section: Synthesis Of Hierarchical 12‐mr Zeolitesmentioning
confidence: 99%
“…[ 348 ] These results were also obtained by the second group who obtained an improved crystallinity and thermal stability in the synthesis of hollow beta zeolite nanocrystals. [ 345 ] Tetrapropylammonium hydroxide/bromide (TPAOH, TPABr) was used by multiple groups, [ 349–351 ] as is the case for tetrabutylammonium hydroxide/bromide (TBAOH, TBABr) [ 352 ] and cetyltrimethylammonium hydroxide/bromide (CTAOH, CTABr). [ 353–355 ] Although there is a subtle difference in structure, the overall outcome after use of these mesoporogens was similar.…”
Section: Synthesis Of Hierarchical 12‐mr Zeolitesmentioning
confidence: 99%
“…Zeolites are crystalline aluminosilicate microporous minerals and are considered widely used in many potential applications, such as adsorption, ion exchange, drug delivery, and catalysis [1][2][3][4][5][6][7][8][9]. 2 of 16 In particular, Cs-pollucite is interesting because it has strong basic sites due to the presence of the alkali Cs + cation [10,11].…”
Section: Introductionmentioning
confidence: 99%